Pengaruh Financial Technology, Succession Planning, Financial Self-Efficacy, dan Personality System terhadap Suksesi Bisnis Keluarga (Studi pada UMKM Bisnis Keluarga Sektor Non-Pertanian di Surabaya) - Azhari, Firdania Aulia (Jurnal Ilmu Manajemen, 2021)
Business succession is critical to have for the continuity of family business. This research focuses on the non-agricultural MSMEs managed by families and located in the Surabaya because BPS data shows that the number of MSMEs in the non-agricultural sector in Surabaya is the highest compared to other cities in East Java Province. This research aimed to determine the effect of financial technology, succession planning, financial self-efficacy, and personality systems on family business succession. They are using a sample of 110 respondents of MSME owners from online and offline questionnaires. Data were analyzed using multiple linear regression and processed using SPSS 26. This research shows that the variables financial technology, financial self-efficacy, and personality system have a significant positive effect. In contrast, the variable succession planning has a significant negative effect. It is hoped that the Surabaya government can use the results of this research to improve socialization related to financial technology, financial self-efficacy, and personality systems for the succession of family businesses can be sustainable.